Punishment and the History of Political Philosophy : From Classical Republicanism to the Crisis of Modern Criminal Justice - Shuster, Arthur, 1980- (Book collections on Project MUSE., 2016)
"In Punishment and the History of Political Philosophy, Arthur Shuster offers an insightful study of punishment in the works of Plato, Hobbes, Montesquieu, Beccaria, Kant, and Foucault. Through careful interpretation of their key texts, he argues that continuing tensions over retribution's role in punishment reflect the shift in political philosophy from classical republicanism to modern notions of individual natural rights and the social contract."--